2000
DOI: 10.1520/jte12071j
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Young's Moduli for Lead Zirconate Titanate (PZT) Ceramics

Abstract: Knowledge of the Young's moduli is necessary for piezoelectric ceramics in order to separate the total deformation into an elastic and a plastic contribution. The methods for the determination of the Young's moduli, well known from conventional ceramics, are much more complicated due to the special electrical boundary conditions. The main aim of the report is to discuss the question in which mechanical tests the conditions of a constant electrical field are fulfilled and in which type of test constant dielectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Eq. ( 30) is in the same form as it was derived in our previous work [22] . The motional admittance part of Eq.…”
Section: Derivation Of Analytical Solutions For the Pe With Unpoled S...mentioning
confidence: 87%
See 3 more Smart Citations
“…Eq. ( 30) is in the same form as it was derived in our previous work [22] . The motional admittance part of Eq.…”
Section: Derivation Of Analytical Solutions For the Pe With Unpoled S...mentioning
confidence: 87%
“…From the inequality relationship above, we can conclude that elastic compliance and elastic loss of unpoled piezoelectric ceramic is not simply a statistical average of s D 33 and s D 11 , but "intermediate" between intensive-ness and extensive-ness; the electrical constraint condition of unpoled piezoceramic is not purely D -constant. Relationship 1 was proposed by Fett et al [22] , whereas relationship 2 has not been so widely discussed as long as the authors' knowledge. Only the very recent study [23] demonstrated measurement of elastic loss of unpoled piezoelectric ceramic, but proper discussion was missed.…”
Section: Possible Explanation Of Intermediate Elastic Property Of Unp...mentioning
confidence: 99%
See 2 more Smart Citations
“…The existing literature on the electro-mechanical performance of PZT ceramics was mainly investigated under uniaxial loading, predominantly in compression tests, for the basic design of transducers [1]- [10]. The nonlinear nonsymmetrical deformation behavior in tension and compression was also investigated [11]- [12].…”
Section: Introductionmentioning
confidence: 99%